Addressing Police Occupational Safety During an Opioid Crisis: The Syringe Threat and Injury Correlates (STIC) Score. Issue 1 (January 2020) - Beletsky, Leo; Abramovitz, Daniela; Arredondo, Jaime; Baker, Pieter; Artamonova, Irina; Marotta, Phil; Mittal, Maria Luisa; Rocha-Jimenez, Teresita; Cepeda, Javier A.; Morales, Mario; Clairgue, Erika; Patterson, Thomas A.; et al.
Abstract : Objective: To develop and validate syringe threat and injury correlates (STIC) score to measure police vulnerability to needlestick injury (NSI). Methods: Tijuana police officers ( N = 1788) received NSI training (2015 to 2016). STIC score incorporates five self-reported behaviors: syringe confiscation, transportation, breaking, discarding, and arrest for syringe possession. Multivariable logistic regression was used to evaluate the association between STIC score and recent NSI. Results: Twenty-three (1.5%) officers reported NSI; higher among women than men (3.8% vs 1.2%; P = 0.007). STIC variables had high internal consistency, a distribution of 4.0, a mode of 1.0, a mean (sd) of 2.0 (0.8), and a median (interquartile range [IQR]) of 2.0 (1.2 to 2.6). STIC was associated with recent NSI; odds of NSI being 2.4 times higher for each point increase ( P -value <0.0001). Conclusions: STIC score is a novel tool for assessing NSI risk and prevention program success among police. Abstract : Supplemental Digital Content is available in the text